Identity and Resistance in Mahmoud Darwish's Poem "Bitaqah Hawiyyah": A Roland Barthes Semiotic Analysis - Nurdiana, Putri; Chotimah, Dien Nur (Journal of Authentic Research, 2025)
This study aims to reveal the meanings of identity and resistance in Mahmoud Darwish’s poem Bitaqah Hawiyyah through Roland Barthes’ semiotic approach. This poem represents the collective experience of the Palestinian nation that has lost its land and freedom, yet continues to maintain its existence through language and symbols. Using Barthes’ semiotic theory, the analysis focuses on three levels of meaning: denotative, connotative, and mythological, to trace how signs in the poem construct the ideology of resistance. The research findings show that every element in the poem—from the command “Record! I am an Arab,” mentions of family, land, to stones—has a symbolic function that affirms Palestinian Arab identity and rejects colonial domination. Darwish successfully transforms oppressive administrative language into a tool for self-affirmation and collective awakening. At the mythological level, this poem creates a myth of steadfastness and existential continuity, where identity is not merely a social status but a form of cultural and spiritual resistance. Thus, Bitaqah Hawiyyah becomes a manifestation that language can function as a field of struggle and affirmation of Palestinian national identity.